Do Extraordinary Claims Require Extraordinary Evidence? - Deming, David (Philosophia (Ramat Gan), 2016)
In 1979 astronomer Carl Sagan popularized the aphorism “extraordinary claims require extraordinary evidence” (ECREE). But Sagan never defined the term “extraordinary.” Ambiguity in what constitutes “extraordinary” has led to misuse of the aphorism. ECREE is commonly invoked to discredit research dealing with scientific anomalies, and has even been rhetorically employed in attempts to raise doubts concerning mainstream scientific hypotheses that have substantive empirical support. The origin of ECREE lies in eighteenth-century Enlightenment criticisms of miracles. The most important of these was Hume’s essay On Miracles. Hume precisely defined an extraordinary claim as one that is directly contradicted by a massive amount of existing evidence. For a claim to qualify as extraordinary there must exist overwhelming empirical data of the exact antithesis. Extraordinary evidence is not a separate category or type of evidence--it is an extraordinarily large number of observations. Claims that are merely novel or those which violate human consensus are not properly characterized as extraordinary. Science does not contemplate two types of evidence. The misuse of ECREE to suppress innovation and maintain orthodoxy should be avoided as it must inevitably retard the scientific goal of establishing reliable knowledge.